ANALISIS PEMASANGAN AUTOMATIC METER READING (AMR) SEBAGAI PENDETEKSI AWAL KELAINAN ALAT PENGUKUR DAN PEMBATAS (APP) PADA PELANGGAN BESAR DI PT.PLN (PERSERO) RAYON SUBULUSSALAM KOTA - Bandri, Sepannur; Anthony, Zuriman; Rifky, Rifky (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Measuring electrical energy is an important matter between PLN and its customers. For this reason, PLN uses kWh meters as a tool to measure energy usage for customers. However, the kWh meter used must not only be able to measure, but must also be accurate, precise and easy. Especially for large customers, where special attention is needed for the use of electrical energy. For this reason, PLN has implemented electronic meters that have been installed with the AMR system for large customers. This is intended so that historical electricity usage for large customers can be recorded and monitored properly. Apart from that, the AMR system is also useful as an early detection of abnormalities in electronic meters for large customers by analyzing the data obtained. Through this data, DLPD (List of Subscriptions Needing Attention) can be determined so that customers who experience problems with their electronic meters can be monitored. With this DLPD feature, it really helps PLN employees in analyzing and evaluating the disturbances that occur. Keywords: Automatic Meter Reading, Electronic Meter, DLPD, AMICON